2003
DOI: 10.1080/08910600310014377
|View full text |Cite
|
Sign up to set email alerts
|

Acacia Gum is a Bifidogenic Dietary Fibre with High Digestive Tolerance in Healthy Humans

Abstract: The objective of the present study was to determine whether acacia gum (GUM) is a prebiotic fibre and to evaluate its intestinal tolerance in healthy subjects. The effects of increasing doses of GUM were compared to those of sucrose (SUC) on stool output, concentration of the main bacterial populations in stools, and occurrence and severity of intestinal symptoms (flatulence, bloating, abdominal cramps, diarrhoea). Ingestion of GUM 10 and 15 g/day for 10 days increased total lactic acid-producing bacteria and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…Previous studies have shown that a daily dose of 30 g of GA can be tolerated by most subjects and the main complaint was excessive flatulence [37]. However, this complaint was found to be mild, even at doses >50 g/day.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that a daily dose of 30 g of GA can be tolerated by most subjects and the main complaint was excessive flatulence [37]. However, this complaint was found to be mild, even at doses >50 g/day.…”
Section: Discussionmentioning
confidence: 99%
“…As these beneficial bacteria increase, they occupy more of the “microbiological niches” in the intestine excluding pathogens. This improves the gut mucosal barrier, prevents infections with enteric pathogens or trans-located gut bacteria [22,23]. Prebiotics have a good safety record at levels found in existing food components.…”
Section: Introductionmentioning
confidence: 99%
“…Flatulence or abdominal bloating is reported at doses greater than 20g / day. Abdominal cramps or diarrhoea are reported at doses greater than 50 g / day [23]. …”
Section: Introductionmentioning
confidence: 99%
“…They transit through the upper gastrointestinal tract and reach the colon intact where they are selectively fermented by indigenous bacteria, especially bifidobacteria and lactobacilli [12,15,26,27]. Beneficial bacteria (including bifidobacteria and lactobacilli) possess enzymes needed to metabolize prebiotics, while other bacteria (such as E coli, clostridia and salmonella) do not [15,27]. Consumption of prebiotics by preterm formula fed infants results in an increase of beneficial microorganisms in the colon, decreasing harmful bacteria to the levels found in breastfed infants.…”
Section: Introductionmentioning
confidence: 99%